2023
DOI: 10.3847/1538-4357/acc4c2
|View full text |Cite
|
Sign up to set email alerts
|

The Astrodust+PAH Model: A Unified Description of the Extinction, Emission, and Polarization from Dust in the Diffuse Interstellar Medium

Abstract: We present a new model of interstellar dust in which large grains are a single composite material, “astrodust,” and nanoparticle-sized grains come in distinct varieties including polycyclic aromatic hydrocarbons (PAHs). We argue that a single-composition model for grains larger than ∼0.02 μm most naturally explains the lack of frequency dependence in the far-infrared (FIR) polarization fraction and the characteristic ratio of optical to FIR polarization. We derive a size distribution and alignment function for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 213 publications
0
35
0
Order By: Relevance
“…This polarization level is much higher than the average level of the ISM of P ∼ 15% observed by Planck Collaboration et al (2020), but it is comparable to the observations toward the massive filament DR21 (Ching et al 2022) andG34.43 (Soam et al 2019). Previous modeling of Planck data concluded that a high alignment degree of grains is required to reproduce the observational data (Guillet et al 2018;Hensley & Draine 2023). Therefore, we expect that the higher polarization level observed in the outer regions of massive filaments can be achieved only if grains can be perfectly aligned.…”
Section: On the Role Of Magnetic Relaxation On Rat Alignmentmentioning
confidence: 82%
“…This polarization level is much higher than the average level of the ISM of P ∼ 15% observed by Planck Collaboration et al (2020), but it is comparable to the observations toward the massive filament DR21 (Ching et al 2022) andG34.43 (Soam et al 2019). Previous modeling of Planck data concluded that a high alignment degree of grains is required to reproduce the observational data (Guillet et al 2018;Hensley & Draine 2023). Therefore, we expect that the higher polarization level observed in the outer regions of massive filaments can be achieved only if grains can be perfectly aligned.…”
Section: On the Role Of Magnetic Relaxation On Rat Alignmentmentioning
confidence: 82%
“…G 0 = 1 is defined as the intensity of the radiation field integrated between 6 and 13.6 eV for the standard ISRF. Note the different nomenclature referring to the radiation heating the dust, where U ; 1.6G 0 by Hensley & Draine (2023). The dust models with high G 0 and U are particularly interesting in our work because it represents the ISM under a strong radiation field from star-forming regions.…”
Section: Polarization Spectrum Of Starburst Galaxiesmentioning
confidence: 99%
“…) is the number density of grains with sizes [a, a + da] (we do not assume any subresolution clumping: the density is the number of grains divided by the cell volume). We assume the efficiencies Q ext as computed by Draine & Lee (1984) and Laor & Draine (1993) for silicates and carbonaceous grains, respectively, though in future versions of this code we will implement the newly developed "astrodust" size-dependent extinction properties of dust grains (Hensley & Draine 2023). The wavelength-dependent extinction is:…”
Section: Modeling the Isrfmentioning
confidence: 99%
“…and is usually defined for PAHs containing <10 3 carbon atoms ). Hensley & Draine (2023) relate the number of carbon atoms to the PAH size via:…”
Section: Pah Masses and Q Pah Fractionsmentioning
confidence: 99%
See 1 more Smart Citation